Project Based Learning in Kaiwa VI Learning (Students Semester 116 Academic Year 2021/2022) - Yuniarsih Yuniarsih; Tia Ristiawati; Imroatul Mufidah (LPPM Universitas PGRI Sumatera Barat, 2025)
This study aims to determine the effect of Project Based Learning on improving the presentation skills of C class student who take the Kaiwa VI lesson on the 2021/2022 academic year. This research was motivated by the problem in the Kaiwa VI course, including: the lack of students' ability to think critically in solving a problem, the lack of understand the content of research so that they are not optimal in presenting research results. Project Based Learning is a student-centered learning model to conduct a deep investigation of a topic. The method used is Pre-Experimental Design with the research form of One Group Pretest-Posttest Design. The sample of this research is class C students who take Kaiwa VI courses. The results showed that the use of the Project Based Learning model in the Kaiwa VI course could improve students' presentation skills. This is shown in the results of the posttest data analysis, which is 8.6 points higher than the pretest. Student responses regarding the implementation of the Project Based Learning model are fairly good.